Effect of Bovine Lactoferrin and Casein Peptide Powder on Microbial Growth and Glucose Utilization by Microorganisms in Pork Meat During Storage at 4oC - Umuhumuza, Liliane Clarisse; Wei-Min, Niu; Sun, Xiulan (Pakistan Journal of Nutrition, 2011)
In this research, the effect of Lactoferrin and Casein peptide on antimicrobial activities and glucose utilization by microorganisms in hot-boned (4-5 h after death) pork meat during storage at 4oC for five days was examined. Total plate count was lower for sample with added Lactoferrin and Casein peptide than control sample. Meat sample with added Lactoferrin had lower plate count than sample with added Casein peptide. High Pressure Liquid Chromatography (HPLC) was also used to detect pork meat glucose also known as freshness index of meat and the results showed that glucose content increased during storage from day 1 to day 3 then slightly decreased at day 5 with the addition of Lactoferrin and Casein peptide and the differences were not significant (p